Prácticas tradicionales y el rol turismo espiritual en el manejo de plantas psicotrópicas en la comunidad Kukama de Padre Cocha. Loreto. 2024 - Salvador Huiñapi, John Carlos (2025)
This study, with a quantitative approach and a non-experimental, exploratory, descriptive, explanatory and correlational design, analyzes traditional practices for the management of psychotropic plants and the role of spiritual tourism in the Kukama community of Padre Cocha, Punchana. The research included all 12 people dedicated to the ritual use of plants such as ayahuasca (Banisteriopsis caapi) and chacruna (Psychotria viridis), using intentional sampling. A structured survey was applied with a reliability coefficient of 0.713 (Cronbach's alpha). The statistical analysis, performed with SPSS v26, included the Shapiro-Wilk test and Pearson's correlation. The results show that these plants not only have medicinal uses, but also constitute a spiritual connection with ancestral heritage. Their ceremonial use persists, although it faces threats due to the loss of traditional knowledge and the growing influence of external tourism models. Spiritual tourism is a complex, ritualized, and culturally significant practice, but it requires adequate regulation to avoid the trivialization of the sacred. Although there are economic benefits and potential for cultural appreciation, challenges related to community control, sustainability, and symbolic protection persist. A significant relationship was found between traditional practices and the impacts of spiritual tourism, highlighting the need to strengthen ancestral knowledge. However, no clear correlation was found between challenges and opportunities, highlighting the urgent need for culturally sensitive and technically supported management.